Predictive Uncertainty Analysis of Straightness Error Measurements in Dynamic Measurement Modes - Virostková, Kristína; Derevianko, Anna; Kroupa, Jiří; Marek, Tomáš; Ulrych, Michal; Holub, Michal; Marek, Jiří (IOP Publishing, 2025)
Over the past two decades, considerable progress has been made in both metrology and control systems, enabling more sophisticated approaches to geometric error identification. Static interferometric measurements are accurate but time-consuming. Therefore, this study compares the measurement uncertainty of static and dynamic (continuous) modes of measuring the geometric accuracy of machine tools. At the same time, the measurement noise value of dynamic measurements was quantified as a contribution to the standard uncertainty of type B. The measurements were performed in static and dynamic modes with a Renishaw XL-80 laser interferometer and using angular optics kit. The results of individual measurements were interpreted through the straightness of the linear axes of the two machine tools. The measurement was performed on a small (X-axis length = 754 mm) and a large (Z-axis length = 9134 mm) CNC machine tool with feed rates from 2000 mm/min to 8000 mm/min. The uncertainty budget calculation of the measured straightness consists of the official documentation of the laser interferometer manufacturer and on the other hand the uncertainty of the straightness was determined experimentally. The comparison of the straightness measured by the static and dynamic modes confirmed that the dynamic measurement represents a time-efficient approach to verifying the geometric accuracy, which is practically indispensable for large machines and significantly reduces downtime for smaller machines without significantly reducing the reliability of the results.
Keywords: Prediction; measurement uncertainty; straightness measurement; laser interferometry; large machine tools